2018
DOI: 10.1155/2018/9565240
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Fluid Flow Physics at Micro‐ to Nano‐scale Porous Media Applications in the Energy Sector

Abstract: While there is a consensus in the literature that embracing nanodevices and nanomaterials helps in improving the efficiency and performance, the reason for the better performance is mostly subscribed to the nanosized material/structure of the system without sufficiently acknowledging the role of fluid flow mechanisms in these systems. This is evident from the literature review of fluid flow modeling in various energy-related applications, which reveals that the fundamental understanding of fluid transport at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 279 publications
0
18
0
3
Order By: Relevance
“…In addition, the porosity inside the particles (granules) is also realized during dissociation. Regularities of gas flow through a porous medium are considered in [ 20 ]. The influence of diffusion and heat fluxes, as well as the size of granules, on the dissociation rate is given in [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the porosity inside the particles (granules) is also realized during dissociation. Regularities of gas flow through a porous medium are considered in [ 20 ]. The influence of diffusion and heat fluxes, as well as the size of granules, on the dissociation rate is given in [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, several million gallons of fracturing liquid is injected at high pressure into shale plays (Palisch et al, 2010;Soliman et al, 2012) to create hydraulic fractures and proppants are mixed with the liquid to keep the fractures from closing The injected fracturing liquid triggers a series of liquid-shale interaction processes that are affected by the operational conditions such as injection, flowback, shut-in, and production; spontaneous imbibition is one of such key liquid-shale interactions. Although spontaneous imbibition, in other words liquid uptake by the porous medium without an enforced pressure, is a universal phenomenon in porous media and its diverse applications (Singh and Myong, 2018), its occurrence in shale rocks is understood to a relatively lesser extent because of complex pore structure and heterogeneous properties. Production data shows that, generally for high production wells only 6%-10% of injected water can be recovered during the fracturing process (Vandecasteele et al, 2015) and up to 48% in the entire production history (Nicot et al, 2012;Roychaudhuri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cooper et al 19 reported that in vitro data well matched with the predicted results using the hydrodynamic Navier Stokes method with the first-order slip condition for the range of average pore diameters from 169-220 nm. Singh and Myong 36 reported that neither continuum models nor free-molecular models could be invoked for fluid flow cases when the Knudsen number falls in the intermediate range between the continuum (Kn < 0.01) and free-molecular flow regimes (Kn>10). When the Knudsen number becomes large (Kn > 0.01), the conventional assumptions of no-slip boundary condition, thermodynamic equilibrium, and linear stress-strain relationship fail.…”
mentioning
confidence: 99%